Efficacy and Safety of Bevacizumab Biosimilars Compared With Reference Biologics in Advanced Non-small Cell Lung Cancer or Metastatic Colorectal Cancer Patients: A Network Meta-Analysis - Xu, Xinyi; Zhang, Shengzhao; Xu, Ting; Zhan, Mei; Chen, Chen; Zhang, Chenyu (Frontiers in Pharmacology, 2022)
Background: Bevacizumab biosimilars are slowly making their way into cancer treatment, but the data on their efficacy and safety in cancer patients is still poor. We systematically summarized the current evidence for the efficacy and safety of bevacizumab biosimilars in patients with advanced non-small cell lung cancer (NSCLC) or metastatic colorectal cancer (CRC). Methods: This review made searches of CNKI, VIP, PubMed, Medline (Ovid), Embase, and Cochrane Library (Ovid) for randomized controlled trials of bevacizumab biosimilars treated in adults with advanced NSCLC or metastatic CRC. A pair-wise meta-analysis and a Bayesian network meta-analysis based on the random-effect model were performed to summarize the evidence. We rated the certainty of evidence by the Grading of Recommendations Assessment, Development, and Evaluation frameworks. Results: 10 eligible trials with a total of 5472 patients were included. Seven trials (n=4581) were for the NSCLC population, while three trials (n=945) were for patients with CRC. According to pair-wise meta-analysis, the efficacy (objective response rate: RR 0.98[0.92-1.04], P=0.45; progression-free survival: HR 1.01[0.92-1.10], P=0.85; overall survival: HR 1.06[0.94-1.19], P=0.35) and safety (incidence of grade 3-5 adverse events: OR 1.03[0.91-1.16], P=0.65) of bevacizumab biosimilars were detected to perform no significant difference with reference biologics in patients with NSCLC, so were metastatic CRC patients (objective response rate: RR 0.97[0.87-1.09], P=0.60; overall survival: HR 0.94[0.70-1.25], P=0.66; incidence of grade 3-5 adverse events: OR 0.78[0.59-1.02], P=0.73). Network estimates displayed seven types of bevacizumab biosimilars in the medication regime of NSCLC patients had no significant difference from each other in efficacy and safety. The certainty of the evidence was assessed as low to moderate. Three biosimilars were found to be clinically equivalent to each other in the patients with CRC, evaluated with very low to moderate certainty. Conclusion: In patients with advanced NSCLC or metastatic CRC, the efficacy and safety of bevacizumab biosimilars were found to be comparable to reference biologics and each other.